COMPARATIVE EXAMINATION OF CONVENTIONAL DIRECT SPUTUM AND INDIRECT SEDIMENTATION ON CYTOSPIN TUBERCULOSIS PATIENT SPUTUM SAMPLES - Widodo Widodo; Devi Etivia Purlinda; Ahmad Riadi (Jurnal Riset Kesehatan, 2022)
Microscopic examination of sputum using the Ziehl-Neelsen stain is the gold standard for Tuberculosis (TB), but it must be performed by experts with special skills. The purpose of this study is to accelerate the determination of the microscopic results using the Ziehl-Neelsen stain. This research is an experimental method in which the test sample is treated and the sputum sample is controlled with up to 25 samples. The method development is very important to increase the sensitivity and specificity of the results of TB examination using microscopes. This observation shows that the indirect cytospin method has a narrower reading range on a circle with a diameter of only 7 mm, making it easier for a bacterial count compared to the traditional direct method with a size of 2 x 3 cm oval shape. The results of the microscopic examination were 21 positive specimens and 4 negative specimens. Mycobacterium tuberculosis with Ziehl-Neelsen staining gave the same results with a sensitivity and specificity of 100%.